Where trust lies - Oke, Janette, 1935-; Logan, Laurel Oke (Oke, Janette, 1935- Return to the Canadian West, 2015)
"After teaching in a 1920s mining town in western Canada, Beth Thatcher no longer feels at home among her wealthy family in the East, and her heart is torn between two very different worlds"--Provided by publisher.